Números triangulares - Solís-Palma, Angie (My University, 2022)
Comprender el concepto de números triangulares, dentro del tema de sucesiones. El cuál se complementa con algunos ejercicios.

Understand the concept of triangular numbers, within the topic of sequences. Which is complemented with some exercises.
Keywords: Números; Sucesiones; Álgebra; Geometría; Matemáticas; Numbers; Successions; Geometry; Mathematics